PP.03.15: NIGHTTIME HOME VERSUS AMBULATORY BLOOD PRESSURE AND TARGET-ORGAN DAMAGE. (June 2015) - Andreadis, E.; Agaliotis, G.; Kollias, A.; Achimastos, A.; Stergiou, G.S.
Abstract : Objective: To evaluate the relationship between nighttime blood pressure assessed by home (HBP) or ambulatory (ABP) monitoring with target-organ damage. Design and method: Untreated hypertensives were evaluated with 24-hour ABP (20 min intervals) and HBP monitoring during daytime (6 days, duplicate morning and evening measurements) and nighttime (automated monitoring, 3 nights, 3 hourly measurements/night). Target organ damage was assessed by echocardiographic left ventricular mass index (LVMI), carotid intima-media thickness (cIMT), urine albumin excretion (UAE) and ankle-brachial index (ABI). Results: A total of 131 subjects were analyzed (mean age 52.1 ± 11.9 years, men 58%, diabetics 6.9%, cardiovascular disease 6.1%). Daytime and nighttime HBP were slightly higher than the respective ABP values (mean difference for daytime/nighttime systolic 3.5 [95% CI 1.7, 5.3]/2.6 [0.9, 4.3] mmHg, p < 0.01 for both comparisons; daytime/nighttime diastolic: -0.2 [-1.4, 0.9]/1.3 [0.2, 2.4] mmHg, p = NS/0.02 respectively). There was a strong association between daytime ABP and HBP (r = 0.71/0.72, systolic/diastolic), as well as between the respective nighttime values (r = 0.80/0.79) (all p < 0.01). Both nighttime ABP and HBP were strongly associated with all indices of target-organ damage (Table). In multivariate analyses, LVMI was best predicted (R 2  = 0.26) by nighttime home pulse pressure (PP), age and male gender; cIMT (R 2  = 0.21) by age and nighttime systolic HBP; UAE (R 2  = 0.24) by nighttime systolic HBP; ABI (R 2  = 0.20) by male gender and nighttime home PP. Conclusions: Nighttime HBP appears to be as good as nighttime ABP in terms of its association with target-organ damage. Figure. No caption available.